KASYF SUFISTIK DALAM PERSPEKTIF ULAMA KOTA BANJARMASIN - Arni, Arni (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2009)
This article discusses the views of the ulama of Banjarmasin concerning the Sufi concept of kasyf. The popular opinion in Banjarese society says that anybody who knows unseen and mysterious things is the one who gets kasyf. According to the ulama, however, kasyf means the uncovering of the unseen and the divine mysteries in which one can see and have a dialogue with God through his/her heart. Kasyf is the fruit of consistent pious life, controlling one?s desires, remembrance of God and worshiping Him in seclusion.